The Rate of Using Internet and Fulltext Databases by Academic Members referring to the IT Centre of Kerman University of Medical Sciences - Roghaieh Ershad Sarabi; Ali Mirzazadeh (Kerman University of Medical Sciences, 2007)
Background & Objective: The rate of using new information services such as Internet is an important criterion for the assessment of development This study was designed to determine the rate of using internet and biomedical databases by academic staffs of Kerman Medical University (KMU) and their attitude towards the available services Methods : In this crosssectional study 120 individuals referring to the KMU Information Center during a period of three months (the first semester of 2006) were selected by convenience sampling and examined by a selfreported questionnaire consisted of 4 sections related to the demographic features subjects opinions about the availability of soft/hardware and subjects attitude and practice in regard to using Internet Results : The response rate was 74% About 64% of the subjects had personal computers at home of whom only 535% had internet connection Only 35% of male respondents and 20% of female respondents had access to KMU Internet connection (P=012) Among 97% of subjects who had active email addresses only 213% used KMU email service About 73% of the subjects were using the subscribed fulltext databases of KMU Science direct Ovid Blackwell Image MD and MD Consult were respectively the most used sources According to the subjects Internet connection at home had a significant positive effect on their professional communications and use of email services (P